2020
DOI: 10.1590/s1517-707620200002.1036
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mechanical properties and corrosion resistance of 316L and 304 stainless steel by low temperature plasma cementation

Abstract: Low temperature plasma carburizing treatment of austenitic stainless steels is a carbon surface diffusion process for a surface hardness and corrosion and wear resistance. The process is carried out by introducing a mixture of carbon-containing gases and through the use of low temperatures the resulting cemented layer usually contains a single phase of supersaturated austenite with carbon -S-phase. For the present investigation, austenitic stainless steels AISI 316L and 304 were plasma cemented for 8 hours in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Many hybrid treatments with the use of plasma processes also resulted in higher hardness of the fabricated surface layers, e.g., shot peening (SP) followed by LTPGN or sequential LTPGC and LTPGN (1615–1662 HV or 7.5–11.5 GPa, respectively) [ 17 , 19 ], cold spraying (CS) of 316L steel followed by LTPGN, LTPGC and LTPGNC processes or their various combinations (800–1350 HV) [ 21 ], LTPGN process followed by a multi-arc ion plating (MAIP) (2280 HV) [ 23 ] as well as TiN coatings produced by PVD technique (18.7–26 GPa) [ 23 , 24 ]. Only some of the surface layers, produced using the plasma processes, were characterized by comparable or lower hardness, e.g., the layer fabricated using LTPGN (5–9 GPa) [ 19 ], LTPGC (570–930 HV) [ 27 , 28 ] or CPEN (438 HV) [ 16 ]. The previously used laser surface alloying of austenitic steel [ 57 , 59 ] resulted in diminished hardness (410–480 HV) in comparison with the LSA processes presented in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many hybrid treatments with the use of plasma processes also resulted in higher hardness of the fabricated surface layers, e.g., shot peening (SP) followed by LTPGN or sequential LTPGC and LTPGN (1615–1662 HV or 7.5–11.5 GPa, respectively) [ 17 , 19 ], cold spraying (CS) of 316L steel followed by LTPGN, LTPGC and LTPGNC processes or their various combinations (800–1350 HV) [ 21 ], LTPGN process followed by a multi-arc ion plating (MAIP) (2280 HV) [ 23 ] as well as TiN coatings produced by PVD technique (18.7–26 GPa) [ 23 , 24 ]. Only some of the surface layers, produced using the plasma processes, were characterized by comparable or lower hardness, e.g., the layer fabricated using LTPGN (5–9 GPa) [ 19 ], LTPGC (570–930 HV) [ 27 , 28 ] or CPEN (438 HV) [ 16 ]. The previously used laser surface alloying of austenitic steel [ 57 , 59 ] resulted in diminished hardness (410–480 HV) in comparison with the LSA processes presented in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of LTPGC process on the wear resistance of the layers produced was studied using “ball-on-disc” technique with alumina (Al 2 O 3 ) ball as a counter-sample [ 26 ] or by tribocorrosion test integrating the similar “ball-on-disc” tester with an electrochemical potentiostat [ 27 ]. Whereas the papers [ 25 , 28 ] did not study the wear behavior of low-temperature gas carburized layers. The plasma gas borided layer became the interlayer between the austenitic substrate and the thin nanostructured diamond film [ 29 ], and its wear resistance was not investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative technique, there is the plasma cleaning technology, which has been the object of study of several works [2][3][4][5][6][7] and shown to be an efficient technique in degradation of compounds with different organic functions. Plasma cleaning technologies are already being used in the cleaning of inputs in the semiconductor sectors [8], food industry [9], medical [10,11], sputtering printed circuit boards [12], surface modification [13][14][15][16] and nitriding [17,18]. However, due to the complexity of the plasma environment, it is necessary to obtain more information about the influence of the different species on the degradation of organic functions [19].…”
mentioning
confidence: 99%